The Impact of Microfinance on Poverty and Income Inequality - Lee, Kevin; Miller, Scott; Tippit, Adrian (Journal of Income Distribution®, 2023)
It is generally accepted in the academic literature that economic growth, global free trade and the development of financial services are the main factors that affect poverty and income inequality in emerging market nations. However, there is currently no conclusive evidence to show how social impact investing through the use of microfinance institutions (MFIs) affects poverty and income inequality. This paper examines the impact of MFI outreach after controlling for economic growth, economic development, and the development of financial services. We find that even after controlling for these factors, MFIs can provide an additional reduction in both poverty and income inequality.